CISGENIC BIOLISTIC TRANSFORMATION FOR OBTAINING NEW FORMS OF POTATOES WITH IMPROVED RESISTANCE TO LATE BLIGHT - Malakhova Natalya Petrovna; Skiba Yuriy Aleksandrovich; Maltseva Elina Romanovna; Iskakova Gulnur Ayupovna; Tezekbaeva Botakoz Kulbaevna; Ismagulova Gulnara Akimzhanovna; Nizkorodova Anna Sergeevna (Academic Journal of Physical and Chemical Sciences, 2020)
This article presents the results of application of cisgenic biolistic transformation for the accelerated production of new forms of potato with increased resistance to late blight. The reason for late blight development is the parasitic organism Phytophthora infestans, belonging to oomycetes (pseudo-fungi), which infects valuable agricultural plants. In this study, with the aim of combating P. infestans, a number of experiments on the biolistic transformation of the most common potato varieties Aksor and Nevskiy were carried out in Kazakhstan. Two potato genes – Rpi-vnt1.1 and StREM1.3 – were selected as targets for introduction. Expression of the first gene should be activated, and the expression of the REMORIN1.3 gene should be suppressed. Rpi-vnt1.1 was under the control of Solanum tuberosum polyubiquitin gene promotor (Pat) and Arabidopsis thaliana polyubiquitin 5 gene terminator (ubq5). Knock-down double stranded RNA-hairpin gene construction for StREM1.3 silencing was under the control of Solanum tuberosum phytochrome B gene promotor (phyB) and Arabidopsis thaliana hot-shock protein 18.2 terminator (HSP18.2). Three series of biolistic transformation were carried out, as a result of which 636 regenerated plants of potato varieties Aksor and Nevskiy were obtained. DNA was extracted from the plant material of potato transformant plants in the quality and quantity suitable for PCR analysis for the presence of an insert. PCR analysis was carried out, revealing 52 plants carrying the VNT insert. StREM1.3 silencing gene construction was detected in plant lines by qPCR, based on comparative analysis of of gene expression level and revealed 6 lines with reliably lower StREM1.3 expression level in comparison with wild-type plants.